Analisis Ekologi Sero dalam Menjaga Eksistensi Perairan Laut Selayar - Astuti, Alfiani Dwi; Karima, Rahmawati Nur; Suwarni, Suwarni; Kharisma, Gaby Nanda (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
This study aims to reveal Sero, one of the local wisdom in Selayar that maintained the existence of sea waters in Selayar Islands Regency by using geographical analyses, namely ecological analysis. Each data in the study was obtained using in-depth interview data collection techniques, observation, and documentation. The results of the study showed that through the analysis of human interaction with the environment (Men Ã¢â€ â€ Environment Theme of Analysis), three motives influenced the behavior of Sero fishermen in Bungaiya Village, namely cultural motives, aquatic environmental motives, and socio-economic motives. Three factors affect the catch by Sero fishermen in Bungaiya Village, namely the knowledge of Sero fishermen, Sero location, and Sero fishermen's performance, which were obtained through Human Activities Ã¢â€ â€ Environment Theme of Analysis (analysis of the interaction between human activities and their environment). In Human Activities Ã¢â€ â€ Environment Theme of Analysis (analysis of physical cultural appearance with its environment), it was found that three factors influence the Sero environment, namely fishing activities by Sero fishermen, Sero ownership systems, and local regulations and norms of the fishing community in Bungaiya Village.